2014
DOI: 10.1007/s10965-014-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory effect and mechanical properties of cyanate ester-polybutadiene epoxy copolymer

Abstract: A type of thermal-induced shape memory polymer was fabricated using a new epoxy resin-polybutadiene epoxy (PBEP) and bisphenol A-type cyanate ester in different mass ratios. Mechanical performance, thermal properties, and shape memory behaviors were investigated systematically. This polymer system presented good shape memory properties. The deformation recovery speed increased with the increase in the amount of PBEP. The maximum deformation recovery speed was 0.0128 s , and the minimum value was 0.0073 s −1 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Because of introducing hydrophilic PEG, the hydrophilic of polyurethane foams get improved. Consistent with water uptake data, water contact angle revealed that all samples showed good wetting properties which emphasized hydrophilicity behavior of PUCO, probably attribute to the hydrophilicity of PEG component [33,44]. Differences in the values of contact angles and water uptakes of various polyurethane foams maybe due to the change in NCO/OH ratio.…”
Section: Water Uptake Of Foams and Contact Angle Studysupporting
confidence: 69%
“…Because of introducing hydrophilic PEG, the hydrophilic of polyurethane foams get improved. Consistent with water uptake data, water contact angle revealed that all samples showed good wetting properties which emphasized hydrophilicity behavior of PUCO, probably attribute to the hydrophilicity of PEG component [33,44]. Differences in the values of contact angles and water uptakes of various polyurethane foams maybe due to the change in NCO/OH ratio.…”
Section: Water Uptake Of Foams and Contact Angle Studysupporting
confidence: 69%
“…Therefore, the crystalline domains act as the scaffold, and the deformation of the polymer takes place in the amorphous state. [ 58 ] The difference between these samples clearly indicates that the shape memory behavior strongly depends on the presence of crystallites in the thermosets. By changing the concentration of the PEG and the cross‐linking density of the thermosets can be controlled shape memory behavior.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that if the glass storage modulus of any polymer is more than two times the rubbery storage modulus, then that polymer possesses excellent shape memory characteristics . On the basis of this theoretical consideration, Wang et al , and Ariraman et al developed CE–EP based SMP without adding a crystallizable segment. Wang et al blended the CE and polybutadiene EP (PBEP) by considering that a flexible aliphatic chain containing PBEP would serve as a reversible phase and cross-linked structure of cured CE would serve as a stationary phase.…”
Section: Shape Memory Characteristicsmentioning
confidence: 99%